2022
DOI: 10.3389/fgene.2022.1006151
|View full text |Cite
|
Sign up to set email alerts
|

A novel signature based on pyroptosis-related genes for predicting prognosis and treatment response in prostate cancer patients

Abstract: Background: Pyroptosis is a form of programmed cell death accompanied by specific inflammatory and immune responses, and it is closely related to the occurrence and progression of various cancers. However, the roles of pyroptosis-related genes (PRGs) in the prognosis, treatment response, and tumor microenvironment (TME) of prostate cancer (PCa) remain to be investigated.Methods: The mRNA expression data and clinical information of PCa patients were obtained from the Cancer Genome Atlas database (TCGA) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…From 2011 to 2016, only a meager 32.3% 5-year survival rate was observed in the United States for advanced-stage prostate cancer. 14,15 Therefore, it is crucial to promptly identify innovative prognostic for PCa in order to improve the accuracy of therapy and healthcare management.…”
Section: Discussionmentioning
confidence: 99%
“…From 2011 to 2016, only a meager 32.3% 5-year survival rate was observed in the United States for advanced-stage prostate cancer. 14,15 Therefore, it is crucial to promptly identify innovative prognostic for PCa in order to improve the accuracy of therapy and healthcare management.…”
Section: Discussionmentioning
confidence: 99%
“…CHMP4C has been shown to be up-regulated in a variety of tumors and is related to malignant behavior. CHMP4C as a model gene for pyroptosis was more closely associated with prostate cancer prognosis implying prognostic value of CHMP4C in prostate cancer ( 14 ). High enrichment of CHMP4C in the urine of patients with high Gleason score prostate cancer suggested the potential of CHMP4C as a novel diagnostic marker for prostate cancer ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the role of CHMP4C in prostate cancer is rarely mentioned. Previous studies have shown that CHMP4C is abundantly expressed as a component of extracellular vesicles in patients with high Gleason scores and as a novel signature of pyroptosis that affects the prognosis of prostate cancer patients ( 14 ) ( 15 ). Therefore, further validation of CHMP4C expression in prostate cancer, and whether CHMP4C affects the biological behavior of prostate cancer and the regulatory pathways involved, will help us to identify new biomarkers and new therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…The key genes which may involve in the process of pyroptosis were obtained from the Molecular Signatures Database (MSigDB) [ 19 ] and the previous pyroptosis-related research [ 20 ]. After removing overlapping genes, 52 pyroptosis genes were included ( Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%